Educational opportunities for the girl child in Africa : a necessary revisit of the discrimination factor with reference to Egypt, South Africa and Cameroon - Chofor Che, Christian-Aime (University of Pretoria, 2006)
Prepared under the supervision of Dr. Enid Hill at the Department of Political Sciences, School of Humanities and Social Sciences, The American University in Cairo, Egypt